The Function and the Affecting Factors of the Zebrafish Gut Microbiota - Li, Pingping; Zhang, Jinhua; Liu, Xiaoyi; Gan, Lu; Xie, Yi; Zhang, Hong; Si, Jing (Frontiers in Microbiology, 2022)
Gut microbiota has become a topical issue in unraveling the research mechanisms underlying disease onset and progression. As an important and potential "organ", gut microbiota plays an important role in regulating intestinal epithelial cell differentiation, proliferation, metabolic function and immune response, angiogenesis and host growth. More recently, zebrafish models have been used to study the interactions between gut microbiota and hosts. It has several advantages, such as short reproductive cycle, low rearing cost, transparent larvae, high genomic similarity to humans and easy construction of germ-free (GF) and transgenic zebrafish. In our review, we reviewed a large amount of data focusing on the close relationship between gut microbiotaand zebrafish host health. Moreover, we outlined the functions of gut microbiota in regulating intestinal epithelial cell differentiation, intestinal epithelial cell proliferation, metabolic function and immune response. More, we summarized major factors that can influence the composition and abundance of gut microbiota, which will help us to better understand the significance of gut microbiota in regulating host biological functions and provide options for maintaining the balance of host health.